Can better targeting improve the effectiveness of Ghana's Fertilizer Subsidy Program? Lessons from Ghana and other countries in Africa south of the Sahara - Houssou, Nazaire; Andam, Kwaw S.; Asante-Addo, Collins (International Food Policy Research Institute, 2017)
Despite improvements to the implementation regime of Ghana’s fertilizer subsidy program, this paper shows that considerable challenges remain in ensuring that the subsidy is targeted to farmers who need fertilizer the most. Currently, larger-scale and wealthier farmers are the main beneficiaries of subsidized fertilizer even though the stated goal is to target smallholder farmers with fertilizer subsidies. The experience of other African countries suggests that the effectiveness of fertilizer subsidies can improve with effective targeting of resource-poor smallholders. However, targeting smallholder farmers entails significant transaction costs and may even be infeasible in some cases. Faced with such challenges, Ghanaian policy makers must ponder the question of how to improve the targeting of input subsidy programs in the country. Further research is needed to identify more cost-effective approaches for achieving the goal of targeting.